2015
DOI: 10.14198/jhse.2015.103.07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sociological aspects on the level of physical activity in physical education students

Abstract: Martins, J., Torres, B., Cardoso, J., Costa, A.M., & Honório, S. (2015). Influence of sociological aspects on the level of physical activity in physical education students. J. Hum. Sport Exerc., 10(3), pp.815-826. Adopting and maintaining an active lifestyle for adolescent students, seems to be impaired and influenced by several factors, among them stand out environmental, psychological and social factors. Thus, the general objectives of this study were submitted to study and understand the extent to which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
1
4
0
7
Order By: Relevance
“…Our study also supports previous findings, in which children and adolescents living in lower-SES neighborhoods actively commuted to school frequently [31]. This confirms the assumption that physical activity can be affected by the socioeconomic variables of the neighborhood [49]. Furthermore, there is an association between active commuting in the neighborhood and neighborhood SES.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also supports previous findings, in which children and adolescents living in lower-SES neighborhoods actively commuted to school frequently [31]. This confirms the assumption that physical activity can be affected by the socioeconomic variables of the neighborhood [49]. Furthermore, there is an association between active commuting in the neighborhood and neighborhood SES.…”
Section: Discussionsupporting
confidence: 91%
“…In this sense, it can be seen how these devices implies many of the competence needs developed in the Self-Determination Theory in a similar way to how it is done in sports practice [37], which would justify the relationship between ego-involved climate and the use of video games. In this sense, task-oriented climate could act as a protective factor against this type of maladaptive behaviour [42].…”
Section: Discussionmentioning
confidence: 99%
“…This fact has been corroborated for both fathers and mothers [46,47]; interestingly, there are even authors who have shown how the mother's educational level is linked to a higher probability that her children participate in physical-sports activities [48,49]. Conversely, greater sedentary behaviors in children have also been linked with lower educational levels on the part of the parents [50]. Parents with a high educational level tend to better regulate the time their children spend on activities, highlighting a control of internet use, associated with sedentary behavior [51,52].…”
Section: Introductionmentioning
confidence: 87%